Incorporation of different polymeric additives for polyvinylidene fluoride membrane fabrication and its performance on methylene blue rejection and antifouling improvement - Suriani Abu Bakar (Tanjung Malim, 2023)
Incorporation of different polymeric additives for polyvinylidene fluoride membrane fabrication and its performance on methylene blue rejection and antifouling improvement by Suriani Abu Bakar